Energy-Environmental Planning of Electric Vehicles (EVs): A Case Study of the National Energy System of Pakistan - Anam Nadeem; Mosè Rossi; Erica Corradi; Lingkang Jin; Gabriele Comodi; Nadeem Ahmed Sheikh (Energies, 2022)
Energy-environmental planning for road transportation involves a vast investigation of vehicles’ technologies and electricity production. However, in developing countries where the public transportation sector is growing quickly, energy-environmental planning is urgently needed. This paper evaluates the future electricity demand, as well as fuel consumption and CO2 emissions reduction, due to the operation of an expected increasing number of electric vehicles (EVs) in Pakistan. The planning of EVs up to 2040 is performed with the ePop simulator that calculates the future EVs’ electricity demand, while EnergyPLAN® assesses the expected new power capacities. Two scenarios are investigated by penetrating 30% and 90% of 2/3 electric wheelers and cars by 2030 and 2040 compared to 2020, respectively. To fulfill the expected energy demand, PV in the daytime and the national electric grid at nighttime are here considered. Finally, a 9 GW of PV capacity is needed to satisfy the EVs’ electricity demand of 14.7 TWh/year, and a 0.7 GW power plants capacity is needed to fulfill 4.7 TWh/year by 2040. Consequently, EVs’ charging scenarios at daytime and nighttime are assessed. Results indicated a total reduction of 10.4 Mtonnes of CO2 emissions and 9.1 Mtoe of fuel consumption by 2040 in the transportation sector.